2013
DOI: 10.1590/s1415-790x2013000300020
|View full text |Cite
|
Sign up to set email alerts
|

Accidents at work and living conditions among solid waste segregators in the open dump of Distrito Federal

Abstract: The work of recycling solid waste segregators allows a precarious livelihood, but triggers a disease process that exacerbates their health and well-being. This study aimed to estimate the prevalence of occupational accidents at the open dump in the Federal District and its associated factors. Most segregators have had an accident at work (55.5%), perceived the danger of their working environment (95.0%) and claimed they did not receive personal protective equipment (51.7%). Among other findings, 55.8% ate food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
29

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 9 publications
0
4
0
29
Order By: Relevance
“…Como tal, muitos estudiosos têm transformado o objeto de estudo em alvo de pesquisas na área de saúde do trabalhador. Estudos contemplam o tema estresse (6,(17)(18) , outros abordam a temática fadiga (19)(20) . A atualidade e o crescente número de investigações são um indicativo do interesse dos pesquisadores em identificar situações de adoecimento do trabalhador no contexto do trabalho e propor estratégias de políticas públicas em prol da promoção da saúde desses sujeitos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Como tal, muitos estudiosos têm transformado o objeto de estudo em alvo de pesquisas na área de saúde do trabalhador. Estudos contemplam o tema estresse (6,(17)(18) , outros abordam a temática fadiga (19)(20) . A atualidade e o crescente número de investigações são um indicativo do interesse dos pesquisadores em identificar situações de adoecimento do trabalhador no contexto do trabalho e propor estratégias de políticas públicas em prol da promoção da saúde desses sujeitos.…”
Section: Discussionunclassified
“…Com o propósito de verificar o nível de estresse entre os agentes da limpeza, constatou-se que apenas ¼ dos pesquisados foram classificados com estresse médio. Tais achados contrapõem-se aos resultados de pesquisa realizada com garis de Uiraúna-PB (6) e com catadores de lixo do Distrito Federal (18) , as quais encontraram alto nível de estresse entre os trabalhadores.Contudo, é preciso ficar alerta, pois o estresse ocupacional "acarreta danos físicos, psíquicos, sociais e culturais que se refletem diretamente na vida dos trabalhadores, causando um impacto no seu dia a dia" (17:202) e pode contribuir de modo invisível para a ocorrên-cia de acidentes ocupacionais e à redução da capacidade de trabalho . Ressalta-se que o mesmo pode decorrer das tensões diárias do processo de trabalho as quais os trabalhadores podem estar expostos, dos baixos salários, da realização de tarefas monóto-nas do próprio, do desgaste que os riscos e cargas ambientais de trabalho podempropiciar (21) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Entre los pocos estudios que encontramos en Latinoamérica, un estudio brasilero en recicladores de basura encontró una prevalencia de accidentes de trabajo de 55.5% (Hoefel, 2013), con condiciones de trabajo infantil, y estos accidentes fueron más frecuentes en mujeres, también encontraron que los recicladores tienen acceso a uso de equipos de protección individual (EPI), pero que muy pocos lo usaban (14%) (33).…”
Section: Discussionunclassified
“…A statistically significant association was found between AW and perception of dangerous work environment, household food insecurity, and the presence of fatigue, stress or sadness (p < 0.05). The authors also concluded that the majority of collectors had accidents at work (55.5%), 95% of workers reported being aware that they worked in a dangerous work environment, and 51.7% of workers claimed not having received PPE (Hoefel et al, 2013). The high occurrence of truck accidents at work, particularly accidental falls and lower limb injuries due to the trash compactor at the rear of the truck, was also shown in other studies, thus pointing out the need for more attention to be paid to these workers' health (Santos, Lima, Murta, & Motta, 2009).…”
Section: Occupational Profile and Exposure Of Solid Waste Collectors mentioning
confidence: 98%